PELATIHAN PROSES DESAIN PRODUK DIBANTU GENERATIVE ARTIFICAL INTELIGENCE BAGI SISWI SMA - Devanny Gumulya (LPPM Institut Desain dan Bisnis Bali, 2023)
This journal describes the implementation of a training program for high school students on the process of product design assisted by Generative Artificial Intelligence (AI). The objective of this training is to introduce the students to the product design program and the stages involved in designing a product, as well as to apply Generative AI as a tool to generate innovative design solutions. The underlying issue that prompted this training is the lack of knowledge among high school female students about the product design program. Therefore, this training was conducted to educate them about the product design program and guide them in designing a product, specifically shoes for their friends, with the assistance of generative AI. The approach used in this training follows the stages of the design process: discover, define, develop, and deliver. The results of this training demonstrate an improvement in the students' understanding of product design and its process. They were able to design shoes with the help of Generative AI and produce design solutions that were well-received by their friends. The majority of the students found the training to be highly beneficial. Furthermore, this training successfully supports the digital transformation in education by providing students with the opportunity to utilize AI technology in the learning process and prepare them for future demands. Overall, this training provides valuable insights and yields positive outcomes in the development of design skills for high school female students.